Endothelium modulates electrical field stimulation-induced contractions of Chelonoidis carbonaria aortic rings - Campos, Rafael; Jacintho, Felipe Fernandes; Britto-Júnior, José; Mónica, Fabíola Z.; Justo, Alberto Fernando Oliveira; Pupo, André Sampaio [UNESP]; Moreno, Ronilson Agnaldo; de Souza, Valéria Barbosa; Schenka, André Almeida; Antunes, Edson; De Nucci, Gilberto (Elsevier, 2020)
The role of endothelium in the electrical-field stimulation (EFS)-induced contractions of Chelonoidis carbonaria aorta was investigated. Contractions were evaluated in the presence and absence of L-NAME (100 μM), tetrodotoxin (1 μM), phentolamine (10 and 100 μM), phenoxybenzamine (1 and 10 μM), prazosin (100 μM), idazoxan (100 μM), atropine (10 μM), D-tubocurarine (10 μM) or indomethacin (10 μM). EFS-induced contraction was also carried out in endothelium-denuded rings. EFS-induced contraction was investigated by the sandwich assay. Concentration curves to endothelin-1 (0.1–100 nM) and U46619 (0.001–100 μM) were also constructed to calculate both Emax and EC50. EFS at 16 Hz contracted Chelonoidis aorta, which was almost abolished by the endothelium removal. The addition of L-NAME increased the EFS response (2.0 ± 0.4 and 8.3 ± 1.9 mN). In L-NAME treated aortic rings, tetrodotoxin did not change the EFS-response (5.1 ± 1.8 and 4.9 ± 1.7 mN). Indomethacin, atropine and d-tubucurarine also did not affect the EFS-response. Phentolamine at 10 μM did not change the EFS-induced contraction; however, at 100 μM, reduced it (3.9 ± 1 and 1.9 ± 0.3 mN). Prazosin and idazoxan did not change EFS-induced contractions. Phenoxybenzamine at 1 μM reduced by 76% (9.6 ± 3.4 and 2.3 ± 0.8 mN) and at 10 μM by 90% the EFS response. Immunohistochemistry identified tyrosine hydroxylase in the endothelium and brain, whereas S100 protein was found only in brain. In conclusion, endothelium modulates EFS-induced contractions in Chelonoidis aortic rings and this modulation may be due to endothelium-derived catecholamines, possibly dopamine.
Keywords: Catecholamines; Endothelium; Tetrodotoxin